Clinical significance and functional validation of PPA1 in various tumors. (26th September 2016) - Luo, Dehong; Wang, Guanwen; Shen, Wenzhi; Zhao, Shuangtao; Zhou, Wei; Wan, Lin; Yuan, Liying; Yang, Shuang; Xiang, Rong
Abstract: The aim of the study was to detect PPA1 expression in various tumors and to investigate the relationship between PPA1 expression and clinicopathological parameters to further analyze its clinical significance. Immunohistochemical staining detected PPA1 expression in 305 noncancerous tissues and 675 tumor tissues, which included 12 different tumor types. QPCR and western blot examined PPA1 expression in tumor‐derived cell lines including those derived from liver, breast, lung, and ovarian cancers. Cell proliferation and apoptosis assays were used to investigate PPA1‐regulated cell growth in tumor cells. Finally, a bioinformatics analysis was used to verify the role of PPA1 in carcinogenesis. Among the 12 types of tumors, PPA1 expression was significantly higher in lung and ovarian cancers ( P  < 0.001). In lung cancer, PPA1 expression was associated with tumor size, patients' age, and smoking status, whereas in ovarian cancer, PPA1 expression was associated with pathological grade ( P  < 0.05). Moreover, we found that PPA1 expression was up‐regulated in lung and ovarian cancer cell lines compared with nontumor cells. In addition, suppression of PPA1 expression by RNA interference in lung and ovarian cancer cells showed increased cell apoptosis and decreased cell proliferation, which was mediated by TP53 and p21 signaling. Notably, a bioinformatics analysis was used to verify the function of PPA1 in the development and progression of tumors. PPA1 expression is significantly higher in many tumors, especially those of lung and ovarian origin, which suggests that PPA1 plays an important role in carcinogenesis and in the development of some tumors. Abstract : PPA1 expression is significantly higher in many tumors, especially those of lung and ovarian origin, which suggests that PPA1 plays an important role in carcinogenesis and in the development of some tumors.